2016
DOI: 10.3390/insects7040077
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Tawny Crazy Ant, Nylanderia fulva, an Emergent Ant Invader in the Southern United States: Is Biological Control a Feasible Management Option?

Abstract: The tawny crazy ant, Nylanderia fulva (Mayr) (Hymenoptera: Formicidae), has invaded states of the U.S. including Texas, Louisiana, Mississippi, Alabama, Florida, and Georgia. Native to South America, N. fulva is considered a pest in the U.S. capable of annoying homeowners and farmers, as well as displacing native ant species. As it continues to expand its range, there is a growing need to develop novel management techniques to control the pest and prevent further spread. Current management efforts rely heavily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Precision was 0.1 To verify that our isotope tracer methods could detect resource sharing over 30-m distances, we conducted a proof of concept experiment using a population of tawny crazy ants (Nylanderia fulva ) near College Station, Texas. This species forms a single supercolony throughout its invaded range in North America, in which workers regularly share collected resources with each other and occupy transitory nests (Eyer et al, 2018;Wang et al, 2016). Our results from this experiment confirmed that the isotope tracer is highly successful at detecting sharing in unicolonial populations at distances that were relevant for our study (i.e., up to 28.4m from the treated area; Kjeldgaard et al,unpublished data ).…”
Section: Stable Isotope Analysessupporting
confidence: 75%
“…Precision was 0.1 To verify that our isotope tracer methods could detect resource sharing over 30-m distances, we conducted a proof of concept experiment using a population of tawny crazy ants (Nylanderia fulva ) near College Station, Texas. This species forms a single supercolony throughout its invaded range in North America, in which workers regularly share collected resources with each other and occupy transitory nests (Eyer et al, 2018;Wang et al, 2016). Our results from this experiment confirmed that the isotope tracer is highly successful at detecting sharing in unicolonial populations at distances that were relevant for our study (i.e., up to 28.4m from the treated area; Kjeldgaard et al,unpublished data ).…”
Section: Stable Isotope Analysessupporting
confidence: 75%
“…Field observations in the U.S.A. introduced range revealed that populations consist of dense networks of polygynous nests (0 to 5 reproductive queens, [43]), with ants freely moving among them without any aggression between non-nestmates [44, 45]. No nuptial flights have been observed in the invasive range, suggesting that the invasion front advances by nest fission (or budding), where queens establish new nests with the help of workers within walking distance of the natal nest [41, 46]. However, these studies only used field observations with limited behavioral tests; genetic studies are lacking to clearly determine the population genetics, colony structure and aggression patterns of the tawny crazy ant within its introduced range, and no information is available from the species’ native range.…”
Section: Introductionmentioning
confidence: 99%
“…Pachycondyla harpax usually nests underground in the vicinity of trees (Grüter et al, 2018), and although workers forage primarily on the ground, they can also be found on trees (Rocha et al, 2015). However, if P. harpax attends EFNs on I. edulis and P. gonoachanta trees needs to (Wang et al, 2016). Among the few pairs that were segregated in distribution by environmental filters, the pair of Solenopsis species can also be explained by the divergence in the probabilities of occurrence under the canopies of the different trees.…”
Section: Discussionmentioning
confidence: 99%